Kajian Viktimologi terhadap Korban Tindak Pidana Pencurian: Studi Kasus Pembobolan Kaca Mobil di Kramatwat, Serang (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
Indonesia has experienced a rising trend in criminal activity, with theft emerging as one of the most prevalent forms. This crime has various modes and targets, ranging from theft of ordinary valuables to theft of high-value items, one of which is theft by breaking into car windows targeting the valuables inside (car burglary). The main focus in law enforcement is often only on the perpetrators, so that victims are often neglected and the rights of victims are often not fulfilled. This study explores the phenomenon from a victimology perspective, focusing on cases of car burglary in Kramatwatu. The research method of this study is an empirical legal method involving secondary data research followed by primary data research or direct field data. Findings indicate that victim negligence, such as leaving valuables in a position that can be seen from the outside, contributes to the occurrence of these crimes. Additionally, the study reveals that several victims' rights remain unfulfilled due to shortcomings in the law enforcement process. This underscores the need for a more victim-centered approach within the criminal justice system.